2021
DOI: 10.18844/cjes.v11i4.1171
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between academic achievement and attitudes of the middle school students

Abstract: In this study, the relationship between academic achievement and attitudes towards “technology and design lesson” of the middle school, eighth grade students’  gender, family income level, parent education level attitudes towards technology and design lesson have been investigated, and examined the relationship between attitudes and academic achievement. Eighth-grade total of 98 students selected from 3 middle schools by simple random sampling method has been identified at research in North Cyprus. The data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Furthermore, many studies have supported that content knowledge is highly effective on students’ success (Ball, 1988, 1990; Ball & McDiarmid, 1990; Davis & Simmt, 2006; Harbison & Hanushek, 1992; Hill et al, 2004, 2005; Mullens et al, 1996; Rowan et al, 1997; Rowland et al, 2005; Tchoshanov, 2011). There are also studies which indicated that teachers’ positive attitudes and behaviors toward the topic and students influence student success (Aiken, 1970; Arun, 1998; Aşkar, 1986; Baykul, 1990; Ekizoğlu & Tezer, 2007; X. Ma & Kishor, 1997; Moralı & Saracaloğlu, 1995; Şener, 2001; Tağ, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies have supported that content knowledge is highly effective on students’ success (Ball, 1988, 1990; Ball & McDiarmid, 1990; Davis & Simmt, 2006; Harbison & Hanushek, 1992; Hill et al, 2004, 2005; Mullens et al, 1996; Rowan et al, 1997; Rowland et al, 2005; Tchoshanov, 2011). There are also studies which indicated that teachers’ positive attitudes and behaviors toward the topic and students influence student success (Aiken, 1970; Arun, 1998; Aşkar, 1986; Baykul, 1990; Ekizoğlu & Tezer, 2007; X. Ma & Kishor, 1997; Moralı & Saracaloğlu, 1995; Şener, 2001; Tağ, 2000).…”
Section: Discussionmentioning
confidence: 99%